The Chinese entrepreneurship way : a case study approach - Pérez-Cerezo, Julia (2013 digital library., 2013)
China is the second largest economy in the world, and it stands poised to become the largest. China's geo-political power is also developing at a stunning pace. It has been predicted that China will have more impact on the world over the next 20 years than any other country. The world order as we have known it is changing, and China is becoming its leader. But, contrary to the belief that China's economic "miracle" is solely due to its government, the reality is that it has been fuelled by its people's enormous ambitions and entrepreneurial spirit. Private-owned companies account for about 60% of the country's gross domestic product (GDP) and about 75% of the country's jobs. The real secret to the Chinese economy's outstanding development had most to do with the nature and attitude of the Chinese people